Legal Social Justice in Appointment Non-Definitive Regional Heads toward Welfare State - Siboy, Ahmad; Al-Fatih, Sholahuddin; Triasari, Devi; Tegnan, Hilaire (BESTUUR, 2023)
The process of resolving administrative violations in the appointment of non-definitive regional heads that have not been regulated can threaten democratic values. Likewise, there has not been a judicial institution that has been given special authority to try it. This study aims to provide a regulatory model or settlement of administrative violations in the appointment of non-definitive regional heads in the welfare state. This study is a normative legal research that uses legal theory to settle administrative violations, legal protection, the welfare state, and Pancasila democracy. The study results show that the judicial mechanism for appointing non-definitive regional heads has a specificity that cannot be resolved through general State Administrative dispute resolution. In the USA, election disputes were resolved through the courts, whereas, in Australia, the Electoral Management Bodies determine the mayoral elections dispute. A design that can be chosen for the judicial process for appointing a non-definitive regional head is proposed, namely by granting authority to Bawaslu to resolve administrative violations through the Special Court mechanism. The granting of judicial authority can fulfill the basic principles of fast, open, and constitutional non-definitive regional head appointment dispute resolution.